Student-Centered Learning in Islamic Religious Education: A Literature Review of Implementation Strategies and Their Alignment with Islamic Educational Philosophy - Novia Ballianie; Zainal Berlian; Mardeli Mardeli; M Robbani; Mutia Dewi; Sabina Rahmawati (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to analyze the strategies of Islamic Religious Education (IRE) learning based on Student-Centered Learning (SCL). The research employed a qualitative approach using the library research method to analyze and synthesize the literature related to SCL-based Islamic Religious Education learning strategies. The data were collected from scholarly journals, books, and academic documents and analyzed using content analysis through the stages of identification, selection, interpretation, and synthesis, while ensuring validity through source triangulation. The findings indicate that Student-Centered Learning is a relevant instructional approach for improving the quality of Islamic Religious Education, as it positions students as active participants in constructing knowledge, developing skills, and fostering Islamic character. The implementation of various instructional strategies, including Problem-Based Learning, Project-Based Learning, Inquiry Learning, Discovery Learning, Contextual Teaching and Learning, cooperative learning, experiential learning, and authentic assessment, has been shown to enhance learning motivation, critical thinking, creativity, communication, collaboration, and problem-solving skills. This approach also strengthens the internalization of Islamic values through meaningful learning experiences. The successful implementation of SCL is influenced by teachers' competencies, students' readiness, curriculum support, learning facilities and infrastructure, school culture, and the integration of digital technology. Therefore, SCL serves as an effective strategy for developing innovative, contextual, and responsive Islamic Religious Education learning that meets the demands of twenty-first-century education